The aberrantly expressed long non‐coding RNA in the substantia nigra and corpus striatum of Nrf2‐knockout mice. Issue 1 (6th September 2017) - Liu, Jian; Xu, Yali; Kang, Yunxiao; Cao, Shanhu; Shi, Geming; Cui, Huixian; Sun, Shaoguang; Wang, Lei
Abstract: Nuclear factor erythroid 2 like 2 (Nrf2) functions as a neuroprotective agent in Parkinson's disease (PD). This study aimed to investigate the key long non‐coding RNAs (lncRNAs) correlated with Nrf2, which might provide valuable information for the exploration of pathogenesis of PD. The lncRNA and mRNA expression profiling of substantia nigra and corpus striatum of Nrf2 (−/−) mice model was obtained from microarray analysis. The animal experiments conducted for this study were approved by the ethics committee of Hebei Medical University. Bioinformatics analyses were conducted, including differentially expressed lncRNAs/mRNA (differentially expressed lncRNA, DEL/differentially expressed mRNA, DEM) identification, DEL‐DEM coexpression network construction, and biological functions prediction. Quantitative real‐time polymerase chain reaction (qRT‐PCR) was subjected to validate abnormally expressed DELs and DEMs in the substantia nigra and corpus striatum of Nrf2 (−/−) mice model. A total of 48 DELs (37 down‐regulated and 11 up‐regulated) were identified both in Nrf2 (−/−) substantia nigra and corpus striatum; 96 DEMs and 643 DEMs were identified in the substantia nigra and corpus striatum, respectively. DEL‐DEM coexpressed network was constructed. LncRNA AK076880, AK036620, and AK020330 had high connectivity with DEMs both in the substantia nigra and corpus striatum. These DEMs were significantly enriched in signaling pathways such as the calcium signaling pathway, Huntington's disease, Alzheimer's disease, mitogen‐activated protein kinase (MAPK) signaling pathway, and the Wnt signaling pathway. Generally, qRT‐PCR validation results of selected DEMs and DELs were consistent with microarray data. The dysregulated DELs and DEMs in the substantia nigra and corpus striatum of Nrf2 (−/−) mice were identified. Our results might provide useful information for further exploring the pathogenesis mechanism of PD. Abstract : Nuclear factor erythroid 2 like 2 (Nrf2) plays an important role in Parkinson's disease. The long non‐coding RNAs (lncRNA) and mRNA expression profiling of substantia nigra and corpus striatum in Nrf2 (−/−) mice and Nrf2 (+/+) mice model was obtained from microarray analysis. Compared to Nrf2 (+/+) mice, we obtained the differentially expressed lnRNAs/mRNAs (DELs/DEMs) in substantia nigra and corpus striatum of Nrf2 (−/−) mice. Based on the coexpression DEL‐DEM network, functional annotation and qRT‐PCR validation of expression, we obtained key DELs and DEMs in Nrf2 (−/−) mice. Our results might provide useful information for further exploring the pathogenesis mechanism of Parkinson's disease.